Analysis of Intellectual Property Rights as an Object of Fiduciary Guarantee on Banking Credit - Hentriawan, Luki; Prastyanti, Rina Arum; Hastuti, Indra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This writing aims to analyze Intellectual Property Rights as an object of fiduciary guarantee, which until now cannot be said to be maximal, because banks and guarantee institutions have not been able to accept copyright patent rights as fiduciary collateral. There are no clear methods and regulations regarding the basis of Intellectual Property Rights themselves, one of which is regarding the value of the rights attached to intellectual property. This paper discusses the issue of intellectual property rights as an object of fiduciary collateral for credit in banking and how in the future patents and copyrights can be used as objects of fiduciary collateral in banking properly. The theories used in analyzing the problem are legal system theory, ownership theory and fiduciary guarantee theory. The method used in this research is normative legal research which was carried out as an effort to obtain the data needed for the problem. The data used is secondary data and tertiary legal materials. The primary data is used as supporting secondary legal material. And data analysis was carried out using qualitative juridical analysis methods. From the results of this research, it can be seen how the position of patents and copyrights as intangible assets should be used as objects of fiduciary guarantees in banking, by adding the words Intellectual Property Rights regarding guarantees to the Bank Indonesia Regulations (PBI). And what is the concept of examination and assessment of the economic value of intellectual property rights, especially patents and copyrights, which will be used as a reference in calculating financial and legal risks for collateral recipients in future implementation.